Pengaruh Kompetensi Guru terhadap Motivasi Berprestasi Siswa (Studi pada Siswa SdSN Tebet Timur 15 Jakarta) - Nur Kholisoh (CommLine, 2015)
The student’s motivation to excel could be triggered by a stimulus from the out- side or derived from within the students themselves in their biological process and the stu- dents’ thought. One of the triggering factors of external supports student achievement is the teacher. The assessment of student to the teacher’s competence can motivate students to ex- cel. Teacher’s competence can be judged based on three key areas : 1) cognitive competence related to the ability of teachers in the science mastery, 2) competence of attitude related to the feelings and teachers’predisposition to their profession, attitude towards human faces, attitudes toward the field studies which they teach, as well as attitudes toward renewal, and 3) Competence of behavior (performance) related to the ability of the teacher’s behav- ior related to his duties as a teacher.